CARACTERÍSTICAS Y PROPIEDADES FÍSICO-QUÍMICAS DE LA SALIVA: UNA REVISIÓN (2012)
Saliva is a liquid secreted by the salivary glands, which moistens the mouth. Among the fundamental properties are protection of the oral mucosa and teeth, defense through lysozyme, cooperation in digestion, regulation of pH by function buffer, preventing injuries from excess acids and bases, and cleaning of the mouth through chewing movements that can be effected by wetting of the saliva. Salivary dysfunction as the same reduction in the amount of secretion, or changes in chemical concentrations as part of the properties of saliva, is responsible for a large amount of oral and dental problems associated, which have a direct impact on the general health status of the patient. Therefore, it is important to know the characteristics and physicochemical properties of saliva focus of this review.